Lactate Clearance at 24 of Hours as Predictors of Outcome in Children with Shock - Mishra, Bibhudatta; Gyani, Satyen; Mohapatra, Arjit; Mishra, Bishwajit; Patawari, Vidya (European Scientific Journal, ESJ, 2021)
Background: Monitoring of tissue perfusion markers like lactate and its clearance is necessary for early recognition of shock in sick children which will enable the caregiver to initiate an appropriate and timely therapy. Objective: To study the blood lactate clearance at 24 hours of admission and its prognostic importance in predicting the outcomes in children with shock. Methods: This was a “prospective observational” study, conducted in NICU and PICU at Sparsh multispeciality hospital, Bhilai and Jagannath hospital, Bhubaneswar over 80 children presented with shock, from January 2018 to December 2020. Blood lactate level at admission and after 24 hours were evaluated and lactate clearance was compared with mortality. Results: In lactate clearance >20% group, mortality was only 3.8% wherein LC<20% group, mortality was 52.17%. In Lactate clearance < 10% group, inotropes (p0.0002), ventilator support (p-0.0015) were needed more than Lactate clearance > 20% group. When initial lactate >6mmol/dl, 35% of neonates died in comparison to 11.76% in the group having initial lactate <6mmol/dl. The average lactate clearance among the survivors was 28.35% and among the non-survivors was 5.73% (P <0.001). AUC between lactate clearance and mortality was 0.73 suggestive of a good correlation. Conclusion: Lactate clearance of less than 10% at 24 hours of admission showed a good correlation in predicting the mortality in children with shock.